SEISMICITY CHANGES ASSOCIATED WITH THE 2000 EARTHQUAKE SWARM IN THE IZU ISLAND REGION - Huang Q. (My University, 2006)
A statistical method taking into account the information of magnitude, occurrence time and location of earthquakes was applied to the earthquake data (1977-2000) of the Japan Meteorological Agency (JMA) to investigate seismicity changes in the Izu Island region. The analysis indicated that a quiescence anomaly started about 1.5 years before the occurrence of the largest swarm in the summer of 2000 in the Izu Island region. Close investigations of the possible artifacts due to the selection of model parameters and the improvement of the seismological network lead to the conclusion that the above quiescence anomaly is unlikely a man-made change. The further stochastic test using 1000 random earthquake catalogs supports the idea that the above anomaly is significant. The spatial distribution of the seismic quiescence, which is quantified by a newly developed Q-parameter, revealed a clear anomalous region around the epicentral area of the above earthquake swarm. The seismicity revealed by the normalized parameter tends to increase just before the swarm. As the first test of the above statistical method for investigating seismicity changes of earthquake swarms, this study indicates that the increased RTL parameter would be a new potentially useful index for the risk alarm of earthquake swarms. © 2004 Elsevier Ltd. All rights reserved.
Keywords: ACCELERATED SEISMICITY; EARTHQUAKE SWARM; IZU ISLAND REGION; SEISMIC QUIESCENCE; SEISMICITY CHANGES